Association of Polymorphisms in T-Cell Activation Costimulatory/Inhibitory Signal Genes With Allograft Kidney Rejection Risk - Santiago, Jose Luis; Sánchez-Pérez, Luis; Pérez-Flores, Isabel; de la Higuera, Maria Angeles Moreno; Romero, Natividad Calvo; Querol-García, Javier; Urcelay, Elena; Sánchez-Fructuoso, Ana Isabel (Frontiers in Immunology, 2021)
The genes CD28, CD86 and CTLA-4 conform the costimulatory (CD28-CD86) or inhibitory (CTLA-4-CD86) signal in T-cell activation. T-cell immune response has a critical role in allograft rejection, and single nucleotide polymorphisms (SNPs) located in these genes have been widely analyzed with controversial results. We analyzed a group of SNPs located in the three genes: CD28: rs3116496; CD86: rs1129055; and CTLA-4: rs231775 and rs3087243 in a cohort of 632 consecutively recruited kidney transplanted subjects. All polymorphisms were genotyped by TaqMan chemistry and the diagnosis of rejection was confirmed by biopsy and categorized according to the Banff classification. The analyses showed a statistically significant protective effect to T cell-mediated rejection (TCMR) in carriers of the CTLA-4 rs3087243*G allele, especially in patients with TCMR Banff ≥2 in the overall cohort and in patients without thymoglobulin induction therapy. Both associations were corroborated as independent factors in the multivariate analysis. Interestingly, associations with rejection were not found for any SNP in patients with thymoglobulin induction therapy. As expected, considering the major role of these genes in T-cell activation, no effect was observed for antibody-mediated rejection (ABMR). In conclusion, the SNP rs3087243 located in the CTLA-4 gene may be considered a useful independent biomarker for TCMR risk especially for severe TCMR in patients who did no received thymoglobulin induction therapy.